The development of receptive vocabulary in CLIL vs EFL: Is the learning context the main variable?. (July 2020) - Castellano-Risco, Irene; Alejo-González, Rafael; Piquer-Píriz, Ana M.
Abstract: This paper explores the impact of exposure on the development of receptive vocabulary knowledge of L2 learners in two different types of instructional context -mainstream English as a Foreign Language (EFL) and Content and Language Integrated Learning (CLIL). In order to measure vocabulary size, the 2K and academic version of the Vocabulary Levels Test (VLT; Schmitt, Schmitt & Clapham, 2001) were administered to 138 secondary-school learners with different learning backgrounds in terms of language learning approach (CLIL vs. EFL) and amount of exposure to the L2. The data obtained indicate that the amount of input does not play a significant role in the differences between CLIL and EFL learners' receptive vocabulary knowledge, but rather it is the educational context which seems to benefit the CLIL group in terms of vocabulary growth.